1990
DOI: 10.1007/bf01913421
|View full text |Cite
|
Sign up to set email alerts
|

Thermal analysis of complex fluorides

Abstract: A number of fluorometallates has been investigated by thermal analysis to establish the decomposition stoichiometry and to determine the conditions where stable intermediate phases can be isolated. The decomposition reactions of fluorovanadates depend on the atmosphere. For ammonium hexafluorometallates and potassium pentafluoroaquametallates the decomposition temperatures or enthalpies can be correlated to crystal field stabilization energies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
4
0
2
Order By: Relevance
“…Recently, Wang et al and Ghosh et al reported that, when the F − ions are excessive, the β-NaYF 4 nanocubes and nanocrystals can be formed. In the synthesis of the NaLnF 4 crystals, F − anions serve as a reactant as well as a mineralizer and the presence of an excess of F − ions lowers remarkably the crystallization temparature. Therefore, the amount of F − ions affects significantly the crystallization of the product. Keeping hydrothermal conditions the same, the presence of excessive F − favors the growth of the hexagonal NaYF 4 crystals.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Wang et al and Ghosh et al reported that, when the F − ions are excessive, the β-NaYF 4 nanocubes and nanocrystals can be formed. In the synthesis of the NaLnF 4 crystals, F − anions serve as a reactant as well as a mineralizer and the presence of an excess of F − ions lowers remarkably the crystallization temparature. Therefore, the amount of F − ions affects significantly the crystallization of the product. Keeping hydrothermal conditions the same, the presence of excessive F − favors the growth of the hexagonal NaYF 4 crystals.…”
Section: Resultsmentioning
confidence: 99%
“…In the syntheses of NaHoF 4 and NaEuF 4 , F - acts both as a reactant and as a mineralizer. From Table , when the mole ratios F/Ho of mixture was 7, the pure and well-crystallized product was prepared. However, when the mole ratio F/Ho of mixture was 5, unreacted Ho 2 O 3 remained as an impurity.…”
Section: Resultsmentioning
confidence: 99%
“…In the hexagonal phase (P6, Z ¼ 1), however, there are three types of the cationic sites: one is fully occupied by Y 3+ (1a site), the other is randomly occupied by either Y 3+ or Na + (1f site), and the third one is fully occupied by Na + . In synthesis of the NaLnF 4 , F À acts as both a reactant and a mineralizer [25][26][27]. The excess F À dominates the crystallization of the product.…”
Section: Article In Pressmentioning
confidence: 99%